Youth participation and school - De Vargas Gil, Carmem Zeli (Última Década, 2020)
Traditionally, juvenile participation was restricted to the sphere of classical institutions and leftist political parties, which made the theme of democratic participation problematic. However, the juvenile actor of excellence was always the center of the student movement. To amplify the comprehension of these processes, it might be helpful to diminish the distance between school and young people, showing that apathy and disinterest can be a search for other educational contexts. This text, guided by the studies of researchers that have produced knowledge about juvenile participation, points to different profiles which amplify the traditional point of view of political party participation. It is the mission of teachers, especially History teachers, to be aware of such questions, understanding that youth pursues knowledge acquired in different educational spaces, which implies the renovation of content and educational methods. The theoretical mark of this reflection comes from the understanding of juvenile participation in the writings of Rosana Reguillo, Leslie Sema, José Antônio Pérez Islas, Regina Novais and Helena Abramo, and attempts to comprehend the different forms, content and processes of mobilization of contemporary youth. The concept of youths is based upon the sociological investigation of Marília Sposito, Mario Margulis, José Machado Pais and Alberto Melucci, with the objective of articulating the conceptual definitions of the youth with those of participation, and relating these discussions to school. The ideas collected here are meant to instigate discussions and debates between the youth and educators, looking to reframe the meanings attributed to collective juvenile actions found in contemporary society.